Pengembangan bahan ajar IPS berbasis guided inquiry sosiokultural pada kelas IV sekolah dasar - Hartina Dewi (COLLASE (Creative of Learning Students Elementary Education), 2023)
The purpose of this research are 1) describe the characteristics of social studies teaching materials for grade IV elementary schools in Gebog Kudus district, 2) describe the development of social studies teaching materials Guided Inquiry sociocultural based for grade IV elementary schools, 3) describe the legibility of social studies teaching materials Guided Inquiry sociocultural based in learning developed class IV elementary school, and 4) describes the effectiveness of social studies teaching materials based on Guided Inquiry sociocultural in learning activity for grade IV elementary schools developed.This type of research is R&D (Research and Development) research. The result of the product in this research is social studies teaching materials based on sociocultural science. The R&D research design consists of potentials and problems, data collection, product design, product validation, product revision, final product testing, product revision, and final production. Data collection techniques using the method of observation, interviews, questionnaires, tests, and documentation. The qualitative data analysis technique uses a flow analysis model technique consisting of data reduction, data presentation and conclusion drawing / verification. Quantitative data analysis using validity and effectiveness tests.The results of this study indicate that the teaching materials developed are valid and in accordance with sociocultural-guided inquiry learning which is associated with learning with the peculiarities of the student's area of residence. Gain 0.597 in the medium category, higher than the control class which got an average score of 0.236 gain in the low category, the results of the independent sample test obtained tcount = 3.784 > ttable = 1.9905 and sig. (2-tailed) of 0.000 <0.05, it can be found that there is a difference in the average student learning outcomes between the experimental class using inquiry-based social studies teaching materials and the control class without using sociocultural inquiry-based teaching materials.Keywords: parenting style, learning responsibilityÂ